أحكام هجر الزوجة في الفقه الإسلامي: دراسة مقارنة - عمايره، إسماعيل محمد شندي (جامعة القدس المفتوحة, 2015)
يقوم هذا البحث على دراسة موضوع فقهي مهم بعنوان: "أحكام هجر الزوجة في الفقه الإسلامي -دراسة مقارنة"، وقد انبني من ستة مباحث، وخاتمة، كان المبحث الأول في تعريف الهجر، والثاني في حكم هجر الزوجة، والثالث في سبب هجر الزوجة، والرابع في موقع الهجر في علاج النشوز، والخامس في تفسير هجر الزوجة، والسادس في مدة هجر الزوجة، ثم جاءت الخاتمة في النتائج والتوصيات.
This research is fundamental in studying an important jurisprudential subject entitled: The Rulings of the Deserted Wife in Islamic Jurisprudence: A Comparative Study. It consists of six topics, and a conclusion. The first is devoted to the definition of desertion; the second, the ruling of deserting a wife; the third, the reason behind deserting a wife; the fourth, the position of desertion in the treatment of recalcitrance; the fifth, the interpretation of deserting of a wife, and finally, sixth, the duration of desertions. The conclusion consists of the findings and recommendations.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- العلاقات الزوجية -- الخلافات الزوجية -- هجر الزوجة -- المرأة في الإسلام -- حقوق المرأة